Chitosan in-situ grafted magnetite nanoparticles toward mechanically robust and electrically conductive ionic-covalent nanocomposite hydrogels with sensitive strain-responsive resistance. (28th July 2020) - Li, Shi-Neng; Li, Baoqiang; Yu, Zhi-Ran; Gong, Li-Xiu; Xia, Qiao-Qi; Feng, Yujie; Jia, Dechang; Zhou, Yu; Tang, Long-Cheng
Abstract: Hydrogels with a combination of high mechanical properties and excellent electrical conductivity are promising for soft and wearable electronics devices. However, the trade-off between poor strength/toughness and high electrical resistance of the hydrogels severely hamper their practical application in diverse areas. In this work, we reported a facile and effective strategy for fabricating mechanically robust and electrically conductive nanocomposite hydrogels via incorporating chitosan in-situ grafted magnetite nanoparticles combined with multiple ionic-covalent interactions. The obtained nanocomposite hydrogel delivers a remarkable mechanical strength up to 2.33 MPa and high toughness of 18.18 MJ m -3 at a relatively high water content (80 wt%). Based on the creep/recovery experimental results and analysis (Burger's model and Weibull distribution function), the effect of multiple ionic-covalent interactions among the double-networks and chitosan in-situ grafted nanoparticles on the viscoelastic behavior of the hydrogel was discussed and clarified. In addition, the resultant nanocomposite hydrogel exhibits sensitive strain-induced resistance change under both compressive and tensile stress as well as outstanding stability and repeatability, which can accurately and repeatedly monitor both large mechanical deformation (e.g. tensile strain up to 600%) and human behaviors (e.g., motions of joints and facial expressions). This study offers a new scenario to design and develop a mechanically robust hydrogel with sensitive strain-responsive resistance, showing potential applications in electric skin, motion detection, wearable electronics, etc . Highlights: Hydrogels exhibit a well trade-off between mechanical strength and toughness at relative high water content (80 wt%). Nano-reinforcement combined with multiple interactions endows hydrogel prominent mechanical performance. Hydrogels display sensitive strain-induced resistance change under various deformations. A hydrogel sensor can monitor both large mechanical deformation and small human behaviors.